2011
DOI: 10.1007/s00267-011-9698-0
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Analysis and Social-Biophysical Interdependencies for Common Pool Resource Management: La Brava Wetland (Argentina) as a Case Study

Abstract: This article gives an account of the implementation of a stakeholder analysis framework at La Brava Wetland Basin, Argentina, in a common-pool resource (CPR) management context. Firstly, the context in which the stakeholder framework was implemented is described. Secondly, a four-step methodology is applied: (1) stakeholder identification, (2) stakeholder differentiation-categorization, (3) investigation of stakeholders' relationships, and (4) analysis of social-biophysical interdependencies. This methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…On the other hand, Ostrom showed that many traditional societies can initiate collective and cooperative actions for sustainable practices without the involvement of any centralized governance [2]. There are several efforts made to investigate such coupled SES, whether by using specific models [3][4][5][6][7], or by empirical and experimental studies [8][9][10]. Despite all these efforts, the basic social structure and mechanism that underlies these societies remains unexplained, because our understanding on how cooperative actions emerge from them is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ostrom showed that many traditional societies can initiate collective and cooperative actions for sustainable practices without the involvement of any centralized governance [2]. There are several efforts made to investigate such coupled SES, whether by using specific models [3][4][5][6][7], or by empirical and experimental studies [8][9][10]. Despite all these efforts, the basic social structure and mechanism that underlies these societies remains unexplained, because our understanding on how cooperative actions emerge from them is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Citizen involvement is essential in broadening the conceptualization of the values of natural resources (i.e. lakes, wetlands, forests) and in implementing integrated management plans (Klessig 2001;Sheil & Liswanti 2006;Gurung 2007;Conrad & Daoust 2008;Romanelli et al 2011). As part of this local citizen effort, school student's perceptions also should be considered important in dealing with the issues of conservation and sustainable utilization of natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis takes a behavioral, interest, intercalation and interest approach of key actors/stakeholders to understand a system (Romanelli, Massone, & Escalante, 2011). It is urgent to identify stakeholder governance in order to recognize the characteristics of individuals or groups that influence and are influenced by an organization/program (Wagner Mainardes et al, 2012).…”
Section: Stakeholder Analysismentioning
confidence: 99%
“…It is urgent to identify stakeholder governance in order to recognize the characteristics of individuals or groups that influence and are influenced by an organization/program (Wagner Mainardes et al, 2012). This analysis ensures that all interests in a particular area are considered in the planning process (Romanelli et al, 2011).…”
Section: Stakeholder Analysismentioning
confidence: 99%